2019
DOI: 10.1038/s41590-019-0382-5
|View full text |Cite
|
Sign up to set email alerts
|

Bhlhe40 mediates tissue-specific control of macrophage proliferation in homeostasis and type 2 immunity

Abstract: Most tissue-resident macrophage populations develop during embryogenesis, self-renew in the steady-state and expand during type 2 immunity. Whether shared mechanisms regulate the proliferation of macrophages in homeostasis and disease is unclear. Here we found that the transcription factor Bhlhe40 was required in a cell-intrinsic manner for the self-renewal and maintenance of large peritoneal macrophages (LPMs), but not that of other tissue-resident macrophages. Bhlhe40 was necessary for the proliferation, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 59 publications
5
78
0
Order By: Relevance
“…These experiments revealed the downregulation of many proliferation‐associated genes in DKO AMs (Fig EV2B). A similar downregulation was observed in DKO peritoneal macrophages (Fig EV2B), confirming the recently published observations made for Bhlhe40‐deficient peritoneal macrophages (Jarjour et al , ). It was previously suggested that the low expression of the transcription factors Maf and Mafb, which function as negative regulators of macrophage proliferation (Aziz et al , ), contributes to the self‐renewal capacity of AMs (Soucie et al , ).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…These experiments revealed the downregulation of many proliferation‐associated genes in DKO AMs (Fig EV2B). A similar downregulation was observed in DKO peritoneal macrophages (Fig EV2B), confirming the recently published observations made for Bhlhe40‐deficient peritoneal macrophages (Jarjour et al , ). It was previously suggested that the low expression of the transcription factors Maf and Mafb, which function as negative regulators of macrophage proliferation (Aziz et al , ), contributes to the self‐renewal capacity of AMs (Soucie et al , ).…”
Section: Resultssupporting
confidence: 91%
“…These results are consistent with the redundancy between Bhlhe40 and Bhlhe41 observed in other systems (Rossner et al, 2008;Shahmoradi et al, 2015;Kreslavsky et al, 2017). In contrast, the Bhlhe40 deficiency was solely responsible for the competitive disadvantage in peritoneal macrophages (Fig EV1C and D), in line with a recent report (Jarjour et al, 2019). Full-body irradiation can cause damage to lung tissue that could potentially alter properties of the resident phagocytes.…”
Section: Competitive Disadvantage Of Bhlhe40/bhlhe41-deficient Cells supporting
confidence: 92%
See 3 more Smart Citations